Role and estimate of the structural characteristics as factors of innovation activity of casters - E. M. Karpenko (Литьë и металлургия, 2003)
The article is dedicated to the examination of a raw of matters, concerned with the determination of essence and estimation of structure parameters of production plants as factors of their innovation activity. There is determined the essence of structure characteristics from the viewpoint of system approach, shown their role in forming of the enterprise potential, determined the connection with the complex of aims of the latter. The results of the carried out by authors investigation of influence of structure parameters on the level of innovation activity of the enterprises of metallurgical and foundry sub-branch of RB are briefly characterized.